Evaluation of scarification and in vitro culture methods for callus production in the genus Erythrina - Carlini, Isabela Carvalho [UNESP]; Bertão, Mônica Rosa [UNESP]; Moraes, Milena Cristina [UNESP] (Universidade Estadual de Maringa, 2025)
The genus Erythrina (Fabaceae) has been researched due to its tetracyclic alkaloids that have pharmacological properties. Species of Erythrina have the potential to act on the central nervous system, presenting anxiolytic and anticonvulsant properties. Among them, Erythrina verna is particularly known for its anxiolytic and sedative effects, being widely used in traditional medicine. Studies indicate that the species E. speciosa has gastroprotective properties besides its high ornamental value. In vitro culture involves techniques for growing cells, tissues or organs under aseptic conditions, based on culture media containing essential nutrients for development. In addition, different seed scarification techniques and aseptic methods can be employed to achieve better results, which may vary for each species. In this context, the present work aimed to standardize the methodology of ‘callus culture’ in two species of Erythrina, as well as to evaluate the behavior of these plants under in vitro conditions. The methodology employed for in vitro germination of Erythrina verna and E. speciosa seeds was successful, resulting in seedlings with well-developed stem, cotyledons and root, which served as a source of explants for ‘callus culture’. The scarification techniques used were effective in breaking dormancy in both species. Additionally, the sterilization, disinfection, and cleaning processes played a crucial role in the satisfactory in vitro development of the species.
Keywords: Erythrina speciosa, plant tissue; Erythrina verna; germination; tissue culture